1999
DOI: 10.1242/dev.126.20.4537
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of MAP kinase activation and MPF activation in hormone-stimulated maturation of Xenopus oocytes

Abstract: MAP kinase activation occurs during meiotic maturation of oocytes from all animals, but the requirement for MAP kinase activation in reinitiation of meiosis appears to vary between different classes. In particular, it has become accepted that MAP kinase activation is necessary for progesterone-stimulated meiotic maturation of Xenopus oocytes, while this is clearly not the case in other systems. In this paper, we demonstrate that MAP kinase activation in Xenopus oocytes is an early response to progesterone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…We have recently reported that the specific Hsp90 inhibitor geldanamycin (GA) blocks sustained activation of MAP kinase in Xenopus oocytes (Fisher et al, 1999a), although we did not define the molecular target of Hsp90 inhibition. Mos translation is part of a positive feedback loop in which MAP kinase stimulates, and is apparently required for, Mos synthesis (Matten et al, 1996;Howard et al, 1999).…”
Section: Mos Can Be Translated But Is Underphosphorylated and Does No...mentioning
confidence: 98%
See 1 more Smart Citation
“…We have recently reported that the specific Hsp90 inhibitor geldanamycin (GA) blocks sustained activation of MAP kinase in Xenopus oocytes (Fisher et al, 1999a), although we did not define the molecular target of Hsp90 inhibition. Mos translation is part of a positive feedback loop in which MAP kinase stimulates, and is apparently required for, Mos synthesis (Matten et al, 1996;Howard et al, 1999).…”
Section: Mos Can Be Translated But Is Underphosphorylated and Does No...mentioning
confidence: 98%
“…necessary for fertilization (Haccard et al, 1993;Colledge We have recently demonstrated that interference with the et al., 1994;Hashimoto et al, 1994). Mos is inactivated function of Hsp90 prevents activation of MAP kinase in after exit from meiosis (Lorca et al, 1991;Watanabe Xenopus oocyte maturation (Fisher et al, 1999a(Fisher et al, ), but how et al, 1991Roy et al, 1996) and this inactivation is prevention of MAP kinase activation is mediated was not required to allow entry into first mitosis (Abrieu et al, analysed. Here we show that Mos interacts with Hsp90 in 1997; Walter et al, 1997;Bitangcol et al, 1998; the oocyte and that this interaction is necessary for Mos et al, 1998) or, possibly, the first round of DNA activation, and thus for Mos-mediated MAP kinase activareplication in some species (Tachibana et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal induction of meiotic maturation is first evident with the breakdown of the nuclear envelope (also known as germinal vesicle (GV) breakdown), and this is accompanied by a burst in total cellular protein phosphorylation catalyzed by a plethora of protein kinases. In one of the best characterized oocyte model systems, the African clawed frog Xenopus laevis oocyte, these kinases include Aurora, 6,7 CDK1, [10][11][12] CDK2, 13 CDK7/ MO15, 14 Chk2/Cds1, 15 casein kinase 2 (CK2), 16 ERK2, 9,12,[17][18][19][20][21][22] Haspin, 23,24 JNK, 25,26 MEK1, [27][28][29] MEK2, 30 Mos, 13,31,32 p38γ MAPK, 33 PKB/Akt, 34 Plx1, 35 Raf, [36][37][38][39][40] and RSK1 and RSK2. 9,20,38,[41][42][43] cAMP-dependent protein kinase (PKA) 34 and xPAK 44 are protein kinases that become inhibited during frog meiotic maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal induction of meiotic maturation is first evident with the breakdown of the nuclear envelope (also known as germinal vesicle (GV) breakdown), and this is accompanied by a burst in total cellular protein phosphorylation catalyzed by a plethora of protein kinases. In one of the best characterized oocyte model systems, the African clawed frog Xenopus laevis oocyte, these kinases include Aurora, , CDK1, CDK2, CDK7/MO15, Chk2/Cds1, casein kinase 2 (CK2), ERK2, ,, Haspin, , JNK, , MEK1, MEK2, Mos, ,, p38γ MAPK, PKB/Akt, Plx1, Raf, and RSK1 and RSK2. ,,, cAMP-dependent protein kinase (PKA) and xPAK are protein kinases that become inhibited during frog meiotic maturation. Many of these kinases and others (e.g., calmodulin-dependent kinase 2, phosphatidylinositol 3-kinase) are similarly regulated in other oocytes such as from the sea star, clam, mouse, rat, pig, sheep, goat, and cow. ,, In frog oocytes, severa...…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in temperature or the extension of the high temperature, the spindle microtubules aggregation occurs, the spindle will also disappear but will not reappear after the temperature returns to normal, causing irreversible effects on oocytes (16)(17)(18). Besides, studies have shown that intracellular calcium oscillations triggered by sperm penetration during fertilization (19) and Ca 2+ influx induced by mechanical or chemical operation (20) can both lead to decreased kinase activity, activation of oocytes and recovery of meiosis (21). Thus, some study has speculated that ST manipulation in a Ca 2+ free medium may avoid spontaneous activation, but this has not been confirmed (3,22).…”
Section: Introductionmentioning
confidence: 99%